Discipline-related information behaviour research: educational policy implications - Lasić-Lazić, Jadranka (Array, 2007)
Information behaviour patterns are significantly influenced by the ever increasing sophistication of information resources and technological developments. A crucial element of information behaviour research is applied to the design of information literacy strategies. Those are vital in the higher education sector, where students have the opportunity to apply and improve their information behaviour to the specific contexts of various disciplines and professions. The aim of the authors was to lay emphasis on the importance of information behaviour research in the context of new learning paradigms. This paper provides a contribution to this purpose, by comparing diverse generic information behaviour patterns between students from different academic areas, which could be categorized as hard (i.e. electrical engineering) and soft (i.e. philosophy) disciplines. The premis of a potential computer literacy discrepancy between these groups will be investigated and the question, wether these differences affect their information behaviour, adressed. Examination of these areas can alert educational policies and strategies to issues which could support educational reforms and raise the quality of learning.